Atlas of Endometrial Histopathology - Dallenbach-Hellweg, Gisela; Schmidt, Dietmar; Dallenbach, Friederike; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The prime purpose of this atlas is to help the pathologist find, classify and differentially diagnose the changes he is observing. Information on the daily changes during the menstrual cycle and how to date them is essential for recognizing changes caused by abnormal endogenic and iatrogenic hormonal stimuli in functional endometrial disturbances. To provide their patients with the proper hormonal therapy, gynecologists cannot rely on blood samples only because of the constantly fluctuating hormonal levels. A precise functional diagnosis of the endometrial biopsy is the most accurate and best means for assessing hormonal action. Numerous microphotographs explain in detail how to recognize the normal and pathological changes that can develop in the endometrium. The subject of endometritis and the complex endometrial neoplasms and their precursors, with their differential diagnosis as well as their clinical prognosis are covered in detail. To complete the endometrial histopathology, gestational changes are reviewed and illustrated in the last chapter.
to the First Edition -- Technical Remarks -- Normal Endometrium -- Metaplastic Changes -- Circulatory Disturbances -- Functional Disturbances -- Iatrogenic Changes -- Endometritis -- Neoplasms -- Gestational Changes.
Keywords: Medicine; Gynecology; Pathology; Medicine & Public Health; Pathology; Gynecology